Porous Se@SiO(2) nanospheres attenuate ischemia/reperfusion (I/R)-induced acute kidney injury (AKI) and inflammation by antioxidative stress - Zheng, Zhihuang (Int J Nanomedicine, 2018)
OBJECTIVES: Acute kidney injury (AKI) is a growing global health concern, and is associated with high rates of mortality and morbidity in intensive care units. Se is a trace element with antioxidant properties. This study aimed to determine whether porous Se@SiO(2) nanospheres could relieve oxidative stress and inflammation in ischemia/reperfusion (I/R)-induced AKI. METHODS: Male 6- to 8-week-old C57bl/6 mice were divided into four groups: sham + saline, sham + Se@SiO(2), I/R + saline, and I/R + Se@SiO(2). Mice in the I/R groups experienced 30 minutes of bilateral renal I/R to induce an AKI. Porous Se@SiO(2) nanospheres (1 mg/kg) were intraperitoneally injected into mice in the I/R + Se@SiO(2) group 2 hours before I/R, and the same dose was injected every 12 hours thereafter. Hypoxia/reoxygenation (H/R) was used to mimic I/R in vitro. PBS was used as a control treatment. Human kidney 2 cells were seeded into 12-well plates (5×10(5) cells/well) and divided into four groups: control + PBS group, control + Se@SiO(2) group, H/R + PBS group, and H/R + Se@SiO(2) group (n=3 wells). We then determined the expression levels of ROS, glutathione, inflammatory cytokines and proteins, fibrosis proteins, and carried out histological analysis upon kidney tissues. RESULTS: In vitro, intervention with porous Se@SiO(2) nanospheres significantly reduced levels of ROS (P<0.05), inflammatory cytokines (P<0.05), and inflammation-associated proteins (P<0.05). In vivo, tubular damage, cell apoptosis, and interstitial inflammation during AKI were reduced significantly following treatment with porous Se@SiO(2) nanospheres. Moreover, the occurrence of fibrosis and tubular atrophy after AKI was attenuated by porous Se@SiO(2) nanospheres. CONCLUSION: Porous Se@SiO(2) nanospheres exhibited a protective effect in I/R-induced AKI by resisting oxidative stress and inflammation. This suggests that porous Se@SiO(2) nanospheres may represent a new therapeutic method for AKI.